2004
DOI: 10.1093/ajcn/80.5.1246
|View full text |Cite
|
Sign up to set email alerts
|

Glycemia and insulinemia in healthy subjects after lactose-equivalent meals of milk and other food proteins: the role of plasma amino acids and incretins

Abstract: It can be concluded that food proteins differ in their capacity to stimulate insulin release, possibly by differently affecting the early release of incretin hormones and insulinotropic amino acids. Milk proteins have insulinotropic properties; the whey fraction contains the predominating insulin secretagogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
358
5
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(386 citation statements)
references
References 39 publications
21
358
5
2
Order By: Relevance
“…Both whey and casein appear to increase insulin secretion, however, to different extents (73) . This may be due to their effect on gastric emptying, absorption and kinetics, since the insulin responses seemed to correlate with the increase in plasma AA concentration after protein ingestion (74) .…”
Section: Glycaemic Controlmentioning
confidence: 98%
See 1 more Smart Citation
“…Both whey and casein appear to increase insulin secretion, however, to different extents (73) . This may be due to their effect on gastric emptying, absorption and kinetics, since the insulin responses seemed to correlate with the increase in plasma AA concentration after protein ingestion (74) .…”
Section: Glycaemic Controlmentioning
confidence: 98%
“…Milk proteins have been extensively investigated for their insulinotropic and glucose-lowering effects in healthy subjects (73,75,82,83,(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) and to a limited extent in individuals with suboptimal glucose control (100)(101)(102)(103)(104)(105)(106) . The dose varied significantly between studies from as little as 10 g (92,105,106) -51 g (91) .…”
Section: Short-term Studies On Glycaemic Controlmentioning
confidence: 99%
“…The negative influences of dietary proteins on the Keap1a mRNA levels in the PI and MI (not in the DI) may be partly explained by the pantothenic acid of fish. It was reported that increasing protein intake could increase the serum insulin concentrations in humans [12] and insulin could increase pantothenic acid uptake in rat hearts [102]. Pantothenic acid is mainly absorbed in the front part of the fish intestine [103].…”
Section: General Summary: Optimal Dietary Protein Level Improve the Imentioning
confidence: 99%
“…However, no reports at present have investigated the role of dietary proteins on the intestinal immune barriers and its possible mechanisms in fish. In humans, dietary protein supplementation could increase serum insulin concentrations [12]. Ehlers et al [13] found that increasing plasma insulin levels decreased NFkB activity in human mononuclear cells.…”
Section: Introductionmentioning
confidence: 99%
“…Based on means, SD , and anticipated effect sizes from previous studies, sample sizes were determined for group differences in glucose responses to dietary (primarily dairy) interventions (Gannon, Nuttall, Lane, & Burmeister, 1992; Liljeberg Elmstahl & Bjorck, 2001; Nilsson, Stenberg, Frid, Holst, & Bjorck, 2004; Ostman et al., 2001; von Post‐Skagegard et al., 2006). The power calculation for femoral blood flow and vascular conductance was performed on our previous published work because there are no published group data for these variables (Anton et al., 2006b; Dinenno, Tanaka, Stauffer, & Seals, 2001; Dinenno et al., 2001).…”
Section: Methodsmentioning
confidence: 99%